Risk Analysis of Occupational Health and Safety (OHS) The Construction of the Road in Dumai City (Case Study: Sp. Batang – Sp. Kulim, Sp. Batang – Sp. Terminal and Bts. City of Dumai – Duri) - Ulfany, Sofie; Guanawan, Gunawan; Lisya, Mutia (Nusantara Civil Engineering Journal, 2023)
The rapid development of the construction industry brings not only benefits but also risks. This study will analyze the risks and risk controls that occur in the management of occupational safety and health of road construction projects in the City of Dumai. The method used in this study is qualitative by using a decision tree classification algorithm. The results showed that the main determining variable for the frequency of work accidents on the Dumai City road project was getting hit by a mobilized dump truck, while other risks were traffic jams, being hit by a vibro roller, workers' skin exposed to hazardous materials, and inhalation of hazardous material dust with the results of predictive accuracy and the results of the reality on the ground, namely the frequency of work accidents that occurred in the Dumai city road project, namely 66.67%. The risk control is based on the element requirements of the OHSAS 18001: 2007 Occupational Safety Management System, namely substitution, engineering, administrative controls, and personal protective equipment (PPE).